Changes in Liver Function Tests after Laparoscopic Cholecystectomy - Muhammad Sheheryar Asghar, Mohiuddin Saleem, Qurat Ul Ain (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Laparoscopic cholecystectomy (LC) has developed to be the typical treatment for benign diseases of the gallbladder. Though, it was observed that the serum levels of some liver enzymes increased significantly after LC in patients with normal preoperative liver enzyme levels. Objective: The aim of this study was to estimate the consequence of pneumoperitoneum on serum bilirubin concentration and liver enzymes in laparoscopic cholecystectomy compared to open cholecystectomy (OC). Study Design: A prospective case-control study. Place and Duration: In the Department of Surgery of LGH, Lahore for one-year duration from November 2020 to October 2021. Methods: This analysis encompassed 80 patients treated for laparoscopic cholecystectomy and 40 patients treated for open cholecystectomy as a control group in the surgical department. Blood samples were drawn 24-hours before and 24 hours later to surgery for bio-chemical studies. Results: Despite a substantial increase in aspartate aminotransferase (AST), bilirubin, lactate dehydrogenase (LDH) and alanine aminotransferase (ALT) in the postoperative period, no remarkable change in serum alkaline phosphatase was observed in the LC group in comparison to the OC group. Conclusion: It was found that the increase in liver enzymes and serum bilirubin can be accredited to the adverse effect of pneumoperitoneum on hepatic flow of blood. Although these variations do not appear to be significant clinically, caution must be exercised in determining whether to accomplish laparoscopic cholecystectomy in subjects with hepatic impairment.